2007
DOI: 10.1016/j.clon.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell Kinetics

Abstract: Cell kinetic concepts have pervaded radiation therapy since the early part of the 20th century and have been instrumental in the development of modern radiotherapy. In this review, the fundamental radiobiological concepts that have been developed based on cell kinetic knowledge will be revisited and discussed in the context of contemporary radiation therapy. This will include how the proliferation characteristics, variation in sensitivity during the cell cycle and the extent of radiation-induced cell cycle del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 115 publications
1
18
0
Order By: Relevance
“…In many arthropods studied so far (reviewed by Tilton andBrower 1983, Bakri et al 2005), the effect of gamma radiation was found to vary inversely with the developmental stage of the concerned species. It has been argued that there exists a direct relationship between radiosensitivity and the mitotic activity of the individual (Grosch 1962, Proverbs 1969, Pawlik and Keyomarsi 2004, Wilson 2007. Therefore, adults are more radioresistant than the juvenile stages while the eggs are the most sensitive to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In many arthropods studied so far (reviewed by Tilton andBrower 1983, Bakri et al 2005), the effect of gamma radiation was found to vary inversely with the developmental stage of the concerned species. It has been argued that there exists a direct relationship between radiosensitivity and the mitotic activity of the individual (Grosch 1962, Proverbs 1969, Pawlik and Keyomarsi 2004, Wilson 2007. Therefore, adults are more radioresistant than the juvenile stages while the eggs are the most sensitive to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, numerous factors could alter overall DNA repair and cell fate within tumor subpopulations: the relative percentage of oxic or hypoxic or anoxic cells, the relative duration of hypoxic exposure and cell transit times (e.g., proportion of acute to chronic hypoxia), and differential protein function under a range of O 2 levels (e.g., differential biology between 0.0% and 5.0%; ref. 22). These factors need investigation as nonrepaired DNA breaks, as a function of the microenvironment, could activate oncogenes or inactivate tumor suppressor genes and drive a mutator phenotype and aggressive tumor cell phenotypes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Cell loss can occur by different mechanisms, including necrosis, programmed cell death (apoptosis) and shedding of cells. Knowledge of the cell kinetics is important for understanding the growth characteristics of a cell or cell populations in tissues or organisms (Wilson, 2007). Sponges possess most of the core elements of apoptosis, including members of the caspase family (Wiens and Müller, 2006), which are pivotal enzymes in apoptosis (Kumar, 2007).…”
Section: Introductionmentioning
confidence: 99%